IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KOTA BOGOR TERHADAP LAYANAN KONSELING DAN TES SUKARELA PADA CALON PENGANTIN DI KOTA BOGOR DALAM KONTEKS HIV AIDS - yohana wulan rosaria; Sri Wahyuni (Jurnal Pendidikan Kesehatan, 2020)
One of the efforts made by the Regional Government in the context of HIV or AIDS prevention and control is through policies in the form of regulations by drafting a Regional Regulation on HIV or AIDS Prevention and Control by stipulating Bogor City Regional Regulation No. 4 of 2016 concerning the prevention and control of HIV and AIDS in article 12 paragraph 3 regarding the prevention of HIV or AIDS transmission to prospective brides which is stated in article 13 paragraph 3 which reads that every prospective bride and groom is referred to the Puskesmas to do an HIV or AIDS test because of the number of people living with HIV. or AIDS in the city of Bogor is included in the top three cities in West Java. This is due to human interaction from various groups, making Bogor City a potential area that can accelerate the spread of HIV or AIDS, especially through 2 ways, namely unsafe sex and injecting drug abuse.According to Sugiharti 2016, the implementation of a health service can run well or not, it really requires a central government policy which is then translated into local government policies according to the resources owned by each region. Knowing how to implement Bogor City regional regulations on voluntary counseling and testing for prospective brides and grooms in Bogor City in the context of HIV or AIDS is the aim of this study.The conclusion of this study is that there is a need for a mayoral regulation regarding voluntary counseling and testing of prospective brides in the city of Bogor as an effort to reduce the incidence of HIV or AIDS in the city of Bogor and to protect and provide a sense of security and comfort for the health workers concerned in carrying out their duties.